Atenção ao pré-natal, parto e puerpério e experiência positiva: experiência de mulheres - Vieira, Julia Baldi (Universidade Federal de São Carlos, 2023)
The positive experience of pregnancy, childbirth and postpartum is an important perinatal outcome recognized by the World Health Organization, influenced by beliefs, expectations and recibed care. The COVID-19 pandemic has increased vulnerabilities for perinatal care in Brazil and intensified the challenges thar were faced. The objective of this work is to elucidate the perception of women regarding the assistance received in perinatal period, in context of the COVID-19 pandemic. The participants were recruited through an invitation on the social media of the larger projects of which this work is part, “Nascer e COVID” and “Grupo de apoio a gestação, parto, amamentação e maternagem saudáveis”. Data were obtained through semi-structured individual interviews, on an online platform, and narrative analysis used Bardin's Content Analysis methodology. Three thematic categories emerged from the results: “Autonomy support”; “Negatives to autnomy” and “Social support: sharing and acceptance”. The results suggest that throughout perinatal care, women develop a project for pregnancy, labor and birth through the development of autonomy and value assistance centered on their needs. At the same time, they encounter professionals who offer denials and restrict their autonomy, making them feel fragile and dissatisfied with the care. In view of this, they seek complementary care guided by the construction of autonomy and experience of their project. The support network, mainly made up of marital partners and groups of pregnant women, offers sharing and support in times of adversity. The need of developing and practice autonomy to reach and live positive experiences was evidenced.
Pregnancy, birth and postpartum care and positve experience: women's experience
Keywords: Saúde materno-infantil; Assistência perinatal; Assistência centrada no paciente; Autonomia pessoal; Maternal and child health; Perinatal care; Patient-centered care; Personal autonomy; CIENCIAS DA SAUDE::ENFERMAGEM